Listening to a personal music player is associated with fewer but more serious injuries among snowboarders in a terrain park: a case-control study. Issue 1 (8th July 2014) - Russell, Kelly; Meeuwisse, Willem; Nettel-Aguirre, Alberto; Emery, Carolyn A; Gushue, Shantel; Wishart, Jillian; Romanow, Nicole; Rowe, Brian H; Goulet, Claude; Hagel, Brent E
Abstract : Background: Some snowboarders listen to music on a personal music player and the objective was to determine if listening to music was associated with injury in a terrain park. Methods: A case–control study was conducted at a terrain park in Alberta, Canada during the 2008–2009 and 2009–2010 winter seasons. Cases were snowboarders who were injured in the terrain park and presented to either the ski patrol and/or a nearby emergency department (ED). Demographic, environmental and injury characteristics were collected from standardised ski patrol Accident Report Forms, ED medical records and telephone interviews. Controls were uninjured snowboarders using the same terrain park and were interviewed as they approached the lift-line on randomly selected days and times. Multivariable logistic regression determined if listening to music was associated with the odds of snowboard injury. Results: Overall, 333 injured cases and 1261 non-injured controls were enrolled; 69 (21%) cases and 425 (34%) controls were listening to music. Snowboarders listening to music had significantly lower odds of injury compared with those not listening to music (adjusted odds ratio (OR) 0.68; 95% CI 0.48 to 0.98). Snowboarders listening to music had significantly higher odds of presenting to the ED versus ski patrol only compared with those not listening to music (adjusted OR 2.09; 95% CI 1.07 to 4.05). Conclusions: While listening to music decreased the odds of any injury in the terrain park, it increased the odds of an injury resulting in ED presentation.